(untitled) (Educação e Pesquisa, 1999)
The article discusses the issue of mathematics textbooks used in child education analyzing specifically textbooks that deal with problem solving. Twelve series of textbooks were examined, and the analysis was developed around four pivotal aspects: the form of introduction to the concepts of addition and subtraction, the types of problems proposed, the use of illustrations in the description of the problem, and the type of record asked from children. It has been found that the textbooks examined display little variety with respect to the structure of problems. Thus, problems involving addition are limited to structures of combination and transformation, and the majority of subtraction problems are restricted to the structure of transformation. It has been observed that illustrations are often employed to supply the data related to the problem. In many cases, it has been noted that the illustration itself furnishes the answer to the problem. As to the types of record requested from children, it was clear that they are usually limited to writing the data supplied and the answer in predetermined spaces. Frequently the sign of the operation "expected" to solve the problem is indicated. The study concludes that the pre-school textbooks analyzed intend to work with the issue of problem solving but the situations proposed are repetitive and do not stimulate children to develop and contrast different strategies of solution.